2021
DOI: 10.1177/25158414211040887
|View full text |Cite
|
Sign up to set email alerts
|

Subthreshold micropulse laser adjuvant to bevacizumab versus bevacizumab monotherapy in treating diabetic macular edema: one- year- follow-up

Abstract: Purpose: To compare the therapeutic impact of combining intravitreal injections of bevacizumab (IVB) with micropulse laser (MPL) in central diffuse diabetic macular edema (DME) versus IVB monotherapy during 12 months follow-up. Methods: We conducted a retrospective comparative study of 98 treatment-naive eyes (63 patients) with central diffuse DME. The first group of patients (IVB + MPL group, n = 49) was treated with 3 monthly IVB followed by MPL within 1 week after the third injection. Patients were then fol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 43 publications
0
10
0
Order By: Relevance
“…Their combined use was demonstrated, in fact, to significantly reduce the number of anti-VEGF injections while preserving or even improving morpho-functional outcomes. BCVA improvement and a CMT decrease were illustrated in two thirds [ 55 , 56 , 58 61 , 63 ] and in half of the studies considered [ 55 , 58 61 ], respectively, and a stabilization of these features was described in the remaining cases throughout the entire follow-up [ 56 , 57 , 62 64 ].…”
Section: Clinical Applicationsmentioning
confidence: 99%
“…Their combined use was demonstrated, in fact, to significantly reduce the number of anti-VEGF injections while preserving or even improving morpho-functional outcomes. BCVA improvement and a CMT decrease were illustrated in two thirds [ 55 , 56 , 58 61 , 63 ] and in half of the studies considered [ 55 , 58 61 ], respectively, and a stabilization of these features was described in the remaining cases throughout the entire follow-up [ 56 , 57 , 62 64 ].…”
Section: Clinical Applicationsmentioning
confidence: 99%
“…Six studies were followed up for up to 1 year or 48 weeks, with a loading phase for 3 months, 1 dose each month, and followed by Pro Re Nata (PRN) injection of anti-VEGF until 12 month. [ 9 10 11 12 13 14 15 ] A study by Akhlaghi et al . [ 16 ] only followed up until the end of the loading phase, and followed up 1 month after (a fourth month) and a study by Khattab et al .…”
Section: Resultsmentioning
confidence: 99%
“…Different Anti-VEGF agents were used. Three of the studies used intravitreal aflibercept;[ 9 12 15 ] other three studies used intravitreal bevacizumab,[ 13 14 16 ] and two other studies used ranibizumab. [ 10 11 ]…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The patients qualified for micropulse therapy after receiving three initial loading anti-VEGF doses and with a CRT below 400 µm. It was suggested that additional laser treatment could decrease the burden of agent injection frequency with similar functional and anatomical outcomes [75,[78][79][80]82,83,[85][86][87]. However, the study by Akhlaghi et al [77] led to a different conclusion: adjuvant MPLT improved BCVA and CRT in eyes resistant to the bevacizumab therapy.…”
Section: Subthreshold Micropulse Laser Treatment and Intravitreal The...mentioning
confidence: 99%